Investigation of the phytochemical content, antioxidant activities, and antimicrobial properties of the selected South African medicinal plants - Mulalo Emelda Makhubele; Samuel Wale Odeyemi; Tracy Madimabi Masebe; Sogolo Lucky Lebelo (Shahrekord University of Medical Sciences, 2024)
Introduction: The increase in antimicrobial resistance has necessitated the screening of medicinal plants as potential agents for the treatment of microbial infections. The aim of the research was to explore antimicrobial activities of identified local plants, namely: Kigelia africana, Maytenus chasei, Ximenia caffra, and Schrebera alata. Methods: The powdered leaves of the selected plants were extracted using ethanol, hexane, ethyl acetate, methanol, and water as solvents, and phytochemical contents were determined. DPPH (1,1-diphenyl-2-picrylhydrazyl) assay was used to determine the antioxidant activities of the extracts. Plant extracts were tested against bacterial ATCC strains for their antimicrobial properties. Results: Hexane and water extracts of K. africana showed the highest percentage yield (16.15% and 8.85%, respectively). The highest phenolic content was found in water extracts of S. alata (14.07 ± 4.8 mg/g) and ethanol extracts of M. chasei (8.6 ± 1.53 mg/g), while the highest flavonoid content was found in the ethyl acetate extract of M. chasei (997.34 ± 52.04 mg/g). For all the tested plant extracts, the ethanol extract of M. chasei showed the best IC50 value of ± 4.71 µg/mL against DPPH compared to other plant extracts. The water extracts of all the tested plants also showed high antioxidant activities. Extracts of X. caffra and S. alata showed comparable inhibitions to ciprofloxacin (P>0.05) against all tested organisms. Conclusion: The findings of the study suggest that the compounds in the plant extracts contained both antioxidant and antibacterial activities and these plants might be considered for the treatment of bacterial infections.